PELAKSANAAN PERJANJIAN KEMITRAAN PERKEBUNAN KELAPA SAWIT ANTARA PT PAPA AGROTAMA SAWIT DAN KOPERASI UNIT DESA MUFAKAT JAYA MANDIRI DALAM PERSPEKTIF KOMPILASI HUKUM EKONOMI SYARIAH - Fighi Dwi Anggara Yudha; Syahbudi Syahbudi; Ishar Pulungan (Al-Aqad, 2025)
Oil palm plantations represent a strategic sector in Indonesia’s economy and play a vital role in enhancing rural communities’ income. This study aims to examine the legal basis, cooperation model, and terms stipulated in the partnership agreement between PT Papa Agrotama Sawit and Koperasi Unit Desa (Village Unit Cooperative) Mufakat Jaya Mandiri, as well as to analyze its compliance with the principles of Sharia economic law outlined in the Compilation of Sharia Economic Law (KHES). The research employs a descriptive qualitative method with a field-based approach. Data were collected through observation, interviews, and documentation. Primary data were obtained from the cooperative’s treasurer, the company’s plantation manager, and cooperative members, while secondary data were drawn from the partnership agreement and the Compilation of Sharia Economic Law (KHES). Data analysis followed an interactive model involving data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings indicate that the partnership was initiated by the local community’s desire to productively manage customary land. The cooperation model adopted is the nucleus–plasma system, with profit sharing allocated at 63.6% for the company and 36.4% for the cooperative. The agreement’s content aligns with the principles of muzara’ah, musaqah, and mukhabarah contracts as stipulated in the KHES. However, a notable weakness remains regarding the cooperative’s legal status, as it has not yet obtained formal legal entity recognition. Therefore, institutional strengthening of the cooperative is essential to ensure the partnership agreement is valid both under Sharia law and positive (national) law.